2010
DOI: 10.1007/s10336-010-0511-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-bias and timing of natal dispersal in cooperatively breeding Puff-throated Bulbuls Alophoixus pallidus

Abstract: While natal dispersal can have a significant impact on population dynamics, it is typically difficult to quantify. We investigated timing of natal dispersal of the cooperatively breeding Puff-throated Bulbul Alophoixus pallidus in a tropical evergreen forest by modelling the probability of staying in or dispersing from their natal territory whilst taking into account the effects of sex, group size, and the presence of helper(s). Birds did not disperse until the beginning of and during the breeding season follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Similar to other nonmigratory bird species, in both the North Temperate Zone and the Tropics, we detected stronger spatial genetic structure for males than females in Rufous-and-white Wrens (Liebgold et al, 2013;Ribeiro et al, 2012;Sankamethawee et al, 2010;Vangestel et al, 2013;Yáber & Rabenold, 2002). Overall, our results show that tropical species may not be as sedentary as previously thought (Stutchbury & Morton, 2001).…”
Section: Patterns Of Dispersalsupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to other nonmigratory bird species, in both the North Temperate Zone and the Tropics, we detected stronger spatial genetic structure for males than females in Rufous-and-white Wrens (Liebgold et al, 2013;Ribeiro et al, 2012;Sankamethawee et al, 2010;Vangestel et al, 2013;Yáber & Rabenold, 2002). Overall, our results show that tropical species may not be as sedentary as previously thought (Stutchbury & Morton, 2001).…”
Section: Patterns Of Dispersalsupporting
confidence: 86%
“…Many tropical species occupy territories throughout the year (Greenberg & Gradwohl, 1986Morton, Derrickson, & Stutchbury, 2000;Tobias, Gamarra-Toledo, García-Olaechea, Pulgarín, & Seddon, 2011), demonstrate high local recruitment (Gill & Stutchbury, 2006;Woltmann et al, 2012), and are thereby thought to exhibit limited dispersal (Moore, Robinson, Lovette, & Robinson, 2008; but see Van Houtan, Pimm, Halley, Bierregaard, & Lovejoy, 2007). Although sex-biased dispersal has been more commonly studied in temperate species (Clarke et al, 1997;Greenwood & Harvey, 1980;Liebgold et al, 2013), our study adds to the body of work that has demonstrated sex-biased dispersal in tropical species (Berg, Eadie, Langen, & Russell, 2009;Pavlova et al, 2012;Ribeiro, Lloyd, Feldheim, & Bowie, 2012;Sankamethawee et al, 2010;Vangestel, Callens, Vandomme, & Lens, 2013;Williams & Rabenold, 2005;Yáber & Rabenold, 2002). Our direct measurements of natal dispersal distances are comparable to those observed in several other tropical bird species, providing further insight into the movement of young animals living at tropical latitudes (e.g., Martin & Bucher, 1993;Woltmann et al, 2012;Woodworth, Faaborg, & Arendt, 1998).…”
Section: Patterns Of Dispersalmentioning
confidence: 76%
See 1 more Smart Citation
“…In our study, survivorship of puff-throated bulbul adults did not seem to be affected by group size (adults in groups had similar survival to those living in pairs). Our previous work also indicated that group size did not affect juvenile survival (Sankamethawee et al 2009) and that group size did not affect the probability of juvenile dispersal in this population (Sankamethawee et al 2010). These findings suggest that the reason for cooperative breeding in this species is probably more related to the availability of mates and breeding territories rather than food resources.…”
Section: Annual Survival and Environmental Variationmentioning
confidence: 80%
“…In other joint-laying species, numbers of males and females at the nest appear more evenly distributed so the role of the ASR as a driver of sex-differences in care might be less important relative to dispersal (see table 11.1 in Vehrencamp and Quinn 2004). Numerous studies suggest that female-biased dispersal is the norm in these taxa (Greenwood and Harvey, 1982;Koenig et al, 2000;Eikenaar et al, 2008;Sankamethawee et al, 2010), suggesting that males should provide the majority of care. While little is known about sex differences in care by the dominant breeders, it is known that male helpers predominate in these species (Brown, 1987;Cockburn, 1998;Haig, 2000).…”
Section: Discussionmentioning
confidence: 99%